Archaeomineralogy. (2nd ed.) - Rapp, George Robert (Springer, 2017)
With major limitations, the planned scope of this book is a systematic look at the mineral and rock materials that have been used from prehistoric times through the seventeenth century CE. The author has used the end of the seventeenth century as a stopping point because the expansion of the world economy and scientific knowl-edge at that time would have led this book to become two volumes.